The Ligand‐Exchange Reactions of Rod‐Like Au25‐nMn (M=Au, Ag, Cu, Pd, Pt) Nanoclusters with Cysteine – A Density Functional Theory Study. Issue 14 (26th June 2019) - Weng, Shiyin; Lv, Ying; Yu, Haizhu; Zhu, Manzhou
Abstract: The atomic precision of ultrasmall noble‐metal nanoclusters (NMNs) is fundamental for elucidating structure‐property relationships and probing their practical applications. So far, the atomic structure of NMNs protected by organic ligands has been widely elucidated, whereas the precise atomic structure of NMNs protected by water‐soluble ligands (such as peptides and nucleic acid), has been rarely reported. With the concept of "precision to precision", density functional theory (DFT) calculations were performed to probe the thermodynamic plausibility and inherent determinants for synthesizing atomically precise, water‐soluble NMNs via the framework‐maintained two‐phase ligand‐exchange method. A series of rod‐like Au25‐n Mn (M=Au, Ag, Cu, Pd, Pt) NMNs with the same framework but varied ligands and metal compositions was chosen as the modeling reactants, and cysteine was used as the modeling water‐soluble ligand. It was found that the acidity of the reaction remarkably affects the thermodynamic facility of the ligand exchange reactions. Ligand effects (structural distortion and acidity) dominate the overall thermodynamic facility of the ligand‐exchange reaction, while the number and type of doped metal atom(s) has little influence. Abstract : Density functional theory calculations are performed to determine the conditions for synthesizing atomically precise, water‐soluble noble‐metal nanoclusters (NMNs) via the framework‐maintained two‐phase ligand‐exchange method. Rod‐like Au25‐ n M n (M=Au, Ag, Cu, Pd, Pt) NMNs with the same framework but varied ligands and metal compositions are chosen as the modeling reactants while cysteine is used as the modeling water‐soluble ligand.